Dossier Introduction: Contemporary Horror Cinema. Issue 3 (23rd March 2023) - Cottrel, Adam; Michael, Charlie; Rusnak, Stacy
The five essays compiled in this dossier address issues of representation in classic and contemporary horror cinema. Students from the Film program at Georgia Gwinnett College (Lawrenceville, Georgia) consider films by Alfred Hitchcock, Jordan Peele, Wes Craven, Pedro Almodovar, and others. In this brief introduction, the three faculty editors of the dossier discuss the theoretical and cultural stakes of the essays to follow.